Changes in the course of ice phenomena on Morskie Oko in the Tatra Mountains from 1963 to 2012 and the implications for tourism - Pawłowski Bogusław (Limnological Review, 2018)
The article presents changes in the course of ice phenomena on Lake Morskie Oko over 50 years. It comprises detailed data of the course of the main parameters of ice regime of the lake in the years 1963–1970. Such a reference period yielded substantial differences in the obtained values of trends in comparison with the period 1971–2010, which is most common in literature. The trends obtained differed substantially from those describing the years 1971–2010, and the change in the parameters – scaled to a year of the analysed period – was about half the size. Attention was also drawn to the practical aspect of the changes in the duration and thickness of ice cover on the lake. In the years 1963–2012 the period of safe movement on the frozen lake was reduced by only 10 days.